Attitude and Practice of Pulmonary Tuberculosis Patient in Urban Settings in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Pulmonarytuberculosis is a very common disease in both urban and rural settings among the Bangladeshi people.Objective: The purpose of the present study was to assess the attitude and practice of pulmonary tuberculosis patient in urban settings of Sylhet District of Bangladesh.Methodology: This cross sectional study was conducted in the DOTs corner of Sylhet MAG Osmani Medical College, Sylhet, Bangladesh and Sylhet Chest Disease Hospital, Sylhet, Bangladesh during the period from June 2011 to November 2011 for a period of six (6) months. All the patients who were diagnosed as case of pulmonary tuberculosis and were treated with anti-tubercular drugs at DOTs corner who attended in the both Hospitals, Sylhet were selected as study population.Result: A total number of 194 pulmonary tuberculosis patients were recruited for this study. Among the 194 patients, 36(18.6%) patients had good attitudes and practices and 158(81.4%) patients had poor attitudes and practices.Conclusion: In conclusion, majority of the pulmonary tuberculosis patients under DOTs living in the urban area of Sylhet have poor level of attitude and practices.Journal of National Institute of Neurosciences Bangladesh, 2018;4(2): 97-100